Theoretical analysis of professional positions models in social science - Anna Ivanenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The study examines the concept of professional positions of social work. Based on related concepts such as "position", "role", "subjective attitude", "inner position" was formed based on the concept semantic position. The general concept of professional positions, found common conditions and mechanisms that make professional positions by analyzing the results of studies conducted in psychology and pedagogy. The results of studies of the structure and dynamics of the features of this construct identity.